A comprehensive review on operating parameters and different pretreatment methodologies for anaerobic digestion of municipal solid waste. (December 2015) - Jain, Siddharth; Jain, Shivani; Wolf, Ingo Tim; Lee, Jonathan; Tong, Yen Wah
Abstract: Municipal solid waste (MSW) management is becoming a serious issue in all over the world. Anaerobic digestion (AD) is one of the technologies to convert that waste into useful form of energy. But megacities like Singapore having limited resources, cannot fulfill the cow dung or other animal manure requirements in AD. Therefore there is a need to study critically the operating parameters and also the pretreatment technologies available for treating the substrate so that one can get the maximum output with limited input. To fulfill the need, the present paper deals with the review of various operating parameters and their effects on AD. This paper also reviews different pretreatment methods including mechanical, thermal, chemical and biological methods to improve the effectiveness of AD of MSW.